Reproductive healthcare denials among a privately insured population - Hebert, Luciana E. (Prev Med Rep, 2021)
This study aimed to quantify and examine reproductive healthcare denials experienced by individuals receiving employer-sponsored health insurance. We conducted a national cross-sectional survey using probability and non-probability-based panels from December 2019-January 2020. Eligible respondents were adults employed by any Standard and Poor’s 500 company, who received employer-sponsored health insurance. Respondents (n = 1,001) reported whether anyone on their healthcare plan had been denied a reproductive healthcare service in the past five years and details about their denials. We conducted bivariate analyses and multiple logistic regression to estimate factors associated with denials. Eleven percent of respondents (14% of women; 10% of men) reported a denial. Compared to lower-income respondents, those with income ≥ $50,000/year were less likely to experience a denial (aOR = 0.53; 95% CI 0.29–0.97). Compared to respondents who were never married, being married (aOR = 2.33; 95% CI: 1.03–5.30) or cohabiting (aOR = 2.43; 95% CI: 1.03–5.72) significantly increased odds of experiencing a denial. In 38% of cases the patient learned of the denial at a scheduled visit, while 23% learned in an emergency setting, and 13% after the encounter. Individuals covered by employer-sponsored health insurance continue to be denied coverage of preventive services. Employers and insurers can facilitate access to reproductive healthcare by ensuring that their plans include comprehensive coverage and in-network providers offer comprehensive services.